2019
DOI: 10.26599/jnr.2019.9040005
|View full text |Cite
|
Sign up to set email alerts
|

Muse cells and Neurorestoratology

Abstract: Multilineage-differentiating stress-enduring (Muse) cells were discovered in 2010 as a subpopulation of mesenchymal stroma cells (MSCs). Muse cells can self-renew and tolerate severe culturing conditions. These cells can differentiate into three lineage cells spontaneously or in induced medium but do not form teratoma in vitro or in vivo. Central nervous system (CNS) diseases, such as intracerebral hemorrhage (ICH), cerebral infarction, and spinal cord injury are normally disastrous. Despite numerous therapy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…The SCs can restrict secondary injury, reduce inflammation, and secrete paracrine factors to protect surviving neurons. SCs also facilitate axon regeneration, and differentiate into new neurons to replace injured neurons in spinal cord injury (SCI) ( Leng et al, 2019 ; Zhang et al, 2019 ; Feng et al, 2021 ). The results of a phase I clinical trial conducted by Mendonça et al ( Mendonça et al, 2014 ) showed that administration of BMSCs improved behavioral scores, electromyography, and somatosensory evoked potentials.…”
Section: Stem Cells (Scs)mentioning
confidence: 99%
“…The SCs can restrict secondary injury, reduce inflammation, and secrete paracrine factors to protect surviving neurons. SCs also facilitate axon regeneration, and differentiate into new neurons to replace injured neurons in spinal cord injury (SCI) ( Leng et al, 2019 ; Zhang et al, 2019 ; Feng et al, 2021 ). The results of a phase I clinical trial conducted by Mendonça et al ( Mendonça et al, 2014 ) showed that administration of BMSCs improved behavioral scores, electromyography, and somatosensory evoked potentials.…”
Section: Stem Cells (Scs)mentioning
confidence: 99%
“…Central nervous system (CNS) post-traumatic injury often leads to persistent neurological damage and devastating consequences, but there is still a lack of effective methods for its treatment (Leng et al, 2019 ; Tsujioka and Yamashita, 2019 ). It includes traumatic brain injury (TBI) and spinal cord injury (SCI) and is one of the world's major disease burdens (Warnock et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Muse cells migrate to tissues that express sphingosine-1 4 , integrate into damaged tissues in vivo when administered intravenously 5,6 , differentiate into specific cells needed to repair tissues, and survive over 6 months in animals 7,8 . Muse cells stimulate tissue regeneration and restore functions in many animal models of diseases, e.g., liver diseases 1,3,[8][9][10][11] , stroke 7,[12][13][14] , muscle regeneration 1,15,16 , skin regeneration 1,3,8,13,17 , malignant glioma 18 , and myocardial infarction 4,11,19 . No tumors have been reported after in vivo transplantation of Muse cells into animals 5,8,20 .…”
Section: Introductionmentioning
confidence: 99%